2016
DOI: 10.1111/ceo.12672
|View full text |Cite
|
Sign up to set email alerts
|

Impact of age‐related macular degeneration in patients with glaucoma: understanding the patients' perspective

Abstract: Background: The aim of the study is to measure the impact of age-related macular degeneration on vision-related activity limitation and preferencebased status for glaucoma patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…We had insufficient ethnic and racial diversity to consider those factors. We did not evaluate personality type, depressive symptoms, economic status, topical eyedrop therapy, coexistent cataract, or coexistent age-related macular degeneration, which others have reported to influence HRQOL scores . We did not collect longitudinal data on change in HRQOL, but we focused on a single point, including points as short as 1 month since surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We had insufficient ethnic and racial diversity to consider those factors. We did not evaluate personality type, depressive symptoms, economic status, topical eyedrop therapy, coexistent cataract, or coexistent age-related macular degeneration, which others have reported to influence HRQOL scores . We did not collect longitudinal data on change in HRQOL, but we focused on a single point, including points as short as 1 month since surgery.…”
Section: Discussionmentioning
confidence: 99%
“…We did not evaluate personality type, depressive symptoms, economic status, topical eyedrop therapy, coexistent cataract, or coexistent age-related macular degeneration, which others have reported to influence HRQOL scores. [27][28][29][30][31] We did not collect longitudinal data on change in HRQOL, but we focused on a single point, including points as short as 1 month since surgery. We do not know whether the patients who underwent GDD surgery had poor HRQOL prior to that specific surgery and we acknowledge that, in our particular practice, GDDs tend to be used later in the surgical treatment algorithm.…”
Section: Limitationsmentioning
confidence: 99%
“…Similarly, clinicians should have a high index of suspicion while reviewing patients with RPD, paying attention to optic disc morphology for features of NTG, being aware of potential difficulties in diagnosing NTG in patients with AMD. Moreover, there is evidence suggesting patients with AMD and glaucoma pose extra hazards such as increased difficulties walking safely when compared to patients with glaucoma alone [59]. This is not surprising when glaucoma predominantly affects tasks requiring contrast discrimination and peripheral vision/light-dark adaptation [60], while AMD influences tasks involving central vision such as reading and recognising faces [61].…”
Section: Discussionmentioning
confidence: 99%
“…One study by Skalicky and colleagues (2016) included 200 participants with glaucoma, 73 of whom also had some degree of age-related macular degeneration (AMD). 15 The authors found that adjusting to dim lights was one of the GAL-9 items which was significantly more difficult for glaucoma patients without AMD than those with AMD (P = 0.04). All other GAL-9 items with reference to light ("Walking after dark"; "Seeing at night"; and "Going from light to dark room or vice versa") were all more difficult for study participants with glaucoma alone, compared to those with both glaucoma and AMD, although these differences were not statistically significant (P = 0.20, 0.42 and 0.11 respectively).…”
Section: Glaucoma Activity Limitation (Gal-9)mentioning
confidence: 95%